Multiscale Study of Soil Stabilization Using Bacterial Biopolymers - Ramachandran, Asha Latha; Dubey, Anant Aishwarya; Dhami, Navdeep; Mukherjee, Abhijit (2021)
Conventional methods of soil stabilization employing materials, such as lime or cement, have considerable environmental penalties due to their high embodied energy. Alternatives such as biopolymers can significantly alleviate this problem. This paper is the first attempt to reveal the basic mechanism of stabilizing sand using bacterial biopolymer by conducting investigations spanning from microscopic to macroscopic scales. Xanthan gum, a bacterial biopolymer, has been microscopically characterized both as a stand-alone binder and with varying proportions of clay reinforcement. Sand columns have been produced using xanthan gum as the binder with varying quantities of clay. The biopolymer stabilized samples were characterized by strength and water absorption. Although xanthan gum was able to bind the sand, exposure to moisture considerably affected its strength. The addition of clay significantly improved the performance by reinforcing the polymer. The mechanism of stabilization has been revealed through advanced microscopic investigations using scanning electron microscopy, nanoindentation, and atomic force microscopy. The study reveals the potential of bacterial polymerization as a means of sustainable soil stabilization.